2008
DOI: 10.1016/j.ijdevneu.2008.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effect of morphine administration in young rats on the analgesic opioid response in adult life

Abstract: Neonates, infants and children are often exposed to pain from invasive procedures during intensive care and during the post-operative period. Opioid anesthesia and post-operative opioid analgesia have been used in infants and result in clinical benefits. The objectives of this study were to verify the effect of repeated 5 microg morphine administration (subcutaneous), once a day for 7 days in 8-day-old rats, at P8 until P14. To verify the long-term effect of morphine, the animals were submitted to a second exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…Therefore, our results indicate that maternal deprivation may alter supraspinally and spinal pain pathways, principally after a short‐time exposure to the stressor (at P21).Corroborating these data, previous study by our group, using the TFL, showed that male rats at P14 presented an increased response to repeated morphine administration without developing tolerance in relation to P8, which can be related to maturation process of opioid pathway. These same animals, at P80, showed greater morphine analgesia and the classic tolerance opioid (Rozisky et al, 2008). In addition, Weaver and Diorio (2007) showed that neonatal stress leads to a persistent reduction in pain sensitivity in female adult rats (P120), possible due to the greater μ‐opioid receptor binding capacity.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, our results indicate that maternal deprivation may alter supraspinally and spinal pain pathways, principally after a short‐time exposure to the stressor (at P21).Corroborating these data, previous study by our group, using the TFL, showed that male rats at P14 presented an increased response to repeated morphine administration without developing tolerance in relation to P8, which can be related to maturation process of opioid pathway. These same animals, at P80, showed greater morphine analgesia and the classic tolerance opioid (Rozisky et al, 2008). In addition, Weaver and Diorio (2007) showed that neonatal stress leads to a persistent reduction in pain sensitivity in female adult rats (P120), possible due to the greater μ‐opioid receptor binding capacity.…”
Section: Discussionmentioning
confidence: 93%
“…However, at P80, the rats experienced greater morphine analgesia and a classic tolerance effect. In addition, the animals that received morphine from P8 until P14 displayed a longer duration of morphine analgesia at the same age (P80) (Rozisky et al, 2008). Another study by our group showed that animals subjected to repeated morphine exposure during early life (5 μg/day for 7 days s.c. from P8 until P14) showed a hypernociceptive behavior in adult life (Rozisky et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that changing morphine sensitivity in the postnatal period may be a part of a general reorganization in the structure and function of primary afferent synapses, neurotransmitter/receptor expression and function, and excitatory and inhibitory modulation from higher brain centers (Fitzgerald and Howard, 2003; Pattinson and Fitzgerald, 2004). A previous study by our research group showed that newborn rats might be more sensitive to low doses of morphine (Rozisky et al, 2008) because an extensive remodeling of opioid receptor expression takes place in the first 3 postnatal weeks (Beland and Fitzgerald, 2001). The density of binding decreases in the first 3 postnatal weeks, with peak binding at P7, which then falls to adult levels by P21 (Beland and Fitzgerald, 2001).…”
Section: Discussionmentioning
confidence: 99%